Water Treatment Against Salt Accumulation for Circulating Water Supply System - Rashidkhodjaevna, Rikhsikhodjaeva Gulchekhra; Muzaffar, Makhmayusupov (European Journal of Life Safety and Stability (2660-9630), 2022)
The purpose of this work is the scientific substantiation and industrial implementation of methods of protection against corrosion, biofouling and scaling of the equipment of circulating water supply systems while reducing water consumption and wastewater discharge. A method has been developed on the basis of the research, to protect the equipment of the circulating water supply system against salt deposition using caustic soda spontaneously entering the system to protect it. Recommendations are given for pilot tests on the protection of metal structures and heat-exchange equipment of circulating water supply systems for conditionally pure water when operating on water with a mineralization of up to 4 g/l. To protect against corrosion the equipment of circulating water supply systems, into the water of which copper salts enter, an effective inhibitory composition (mg/l) is recommended and implemented: sodium silicate - 25.50, sodium tripolyphosphate - 25.50, synthamide -0.5.1.5.